The Influence Of Community Participation And Management Competence On The Performance Of Bumdes Pasundan In Sukamaju Village, Sumber Harta District, Musi Rawas Regency - Sulistiani, Sulistiani; Anzori , Anzori; Irwanto, Tito (Utami Publisher, 2025)
This study aims to analyze the influence of community participation and managerial competence on the performance of Pasundan Village-Owned Enterprises in Sukamaju Village, Sumber Harta District, Musi Rawas Regency. The main issue addressed is low community participation and suboptimal managerial competence, limiting the performance of BUMDes in improving community welfare. Using a quantitative associative research design, data were collected from 50 respondents, including managers and community members, through Likert-scale questionnaires and analyzed with multiple linear regression using SPSS version 25. The results show significant positive effects of community participation (t = 2.508, p = 0.016) and managerial competence (t = 6.507, p = 0.000) on BUMDes performance. Both variables simultaneously influence performance (F = 38.151, p = 0.000). The determination coefficient (R² = 0.619) explains that 61.9% of performance variation can be attributed to these factors, with the remainder influenced by other variables. The findings emphasize the importance of enhancing community engagement and management competencies to improve the performance and sustainability of BUMDes in fostering inclusive and sustainable rural economic development.